Contemporary leadership models and collaboration in primary schools: a mixed-methods study on school quality - Lushaj, Miranda; Shatri, Venera (Frontiers in Education, 2026)
School leadership plays a central role in shaping school quality, particularly in primary education, where leadership practices directly influence collaboration, organizational climate, and teaching processes. Contemporary leadership models emphasize shared responsibility, professional collaboration, and relational forms of influence as key mechanisms for school improvement. Despite extensive international research on educational leadership, empirical evidence that simultaneously examines leadership models, collaboration-related professional competencies, and perceived school quality remains limited, especially in education systems undergoing structural transition. This study investigates the relationships between contemporary leadership models, teachers’ professional competencies related to collaboration, and perceived school quality in primary schools. A sequential explanatory mixed-methods design was employed. Quantitative data were collected from 100 primary school teachers using a structured questionnaire, and qualitative data were gathered through semi-structured interviews with school principals. Quantitative data were analyzed using descriptive statistics, Spearman’s correlation, and simple linear regression, while qualitative data were analyzed thematically. The findings indicate that contemporary leadership models are significant positive predictors of perceived school quality. In addition, teachers’ professional competencies significantly predict the leadership-related school work environment, explaining a substantial proportion of variance in teachers’ perceptions of organizational climate. Qualitative findings further illustrate how leadership practices are enacted in everyday school contexts, highlighting the importance of collaboration, ethical leadership, and contextual constraints such as limited resources and infrastructural challenges. The study contributes to the literature by providing integrated empirical evidence on the indirect mechanisms through which leadership practices influence school quality, emphasizing the role of collaboration and professional competencies within a leadership-related organizational climate. The findings offer practical implications for leadership development, teacher professional learning, and policy initiatives aimed at strengthening school management and improving primary education outcomes.